2012
DOI: 10.1016/j.ijid.2012.05.352
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of intestinal parasites according to the distribution of the patients gender and parasite species for eight years at the Osmangazi University Medical Faculty in Turkey

Abstract: Background: Intestinal parasite infection is still an important public health problem. In this study, patients (outpatients and in-patients) with various gastrointestinal system complaints presenting at various clinics of theOsmangazi University Medical Faculty, from January 2004-December 2011 were investigated retrospectively for intestinal parasites. Methods: Parasitological examinations were done with nativelugol, cellophane-tape methods and trichrome staining in ambiguous cases. Also modified Erlich-Ziehl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
6
2
3
Order By: Relevance
“…B. hominis, whose pathogenicity is still controversial, was identified as the most prevalent parasite (26.5%) in the present study. It was observed that the prevalence of this parasite was between 0.05-13.1% in certain previous studies, which was lower when compared to the findings of the present study (6,8,13,(16)(17)(18). E. histolytica/E.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…B. hominis, whose pathogenicity is still controversial, was identified as the most prevalent parasite (26.5%) in the present study. It was observed that the prevalence of this parasite was between 0.05-13.1% in certain previous studies, which was lower when compared to the findings of the present study (6,8,13,(16)(17)(18). E. histolytica/E.…”
Section: Discussioncontrasting
confidence: 89%
“…The prevalence of intestinal parasites varies based on the region in Turkey. These parasites are less common (3.6-24.1%) in western Turkey due to better socio-economic standards and educational levels (15)(16)(17)(18). In previous studies conducted in eastern provinces in Turkey, the rate of intestinal parasitosis was reported as 17-63.3% (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Turkey provides a wide range, suitable areas in terms of the climate and geographical conditions likewise socio-economic conditions for parasitic infection [10].In a study for investigating the regional prevalence in our country, the rate of intestinal parasites has been found as 10-34% in the Marmara region, 54-94% in the Black Sea region, 12-40% in the Aegean region, 55-80% in the Mediterranean region, 50-75% in Central Anatolia, 60-94% in the East and 64-96% in the South-eastern Anatolia [11].…”
Section: Discussionmentioning
confidence: 99%
“…7 Taenia enfeksiyonları, tanısal zorlukları nedeni ile normal popülasyonda olduğu gibi immünkompremize hastalarda da sıklıkla atlanabilmektedir. 8 Bu çalışmada, hemodiyaliz hastalarında Taenia saginataya bağlı ishal prezantasyonunun nadir görülmesi ve tanısal zorluklar nedeni ile sunulması amaçlanmıştır.…”
Section: Olgu Sunumu Case Reportunclassified